Обліково-інформаційне забезпечення управління розрахунками з контрагентами - Костякова, Анна Анатоліївна; Костякова, Анна Анатолиевна; Kostyakova, Anna (My University, 2020)
UK: У статті з наукової точки зору розглядається одна із ключових проблем фінансової безпеки підприємства в процесі господарської діяльності, обліку зобов’язань, аналізу та звітності, з точки зору впливу ризиків на систему організації та ведення обліку поточної заборгованості по розрахунках з контрагентами. На підставі детального наукового аналізу обліку й звітності розрахунків з постачальниками та підрядниками, та власних досліджень автор розглядає обліково-інформаційне забезпечення процесу управління розрахунками з контрагентами. Надані науковообґрунтовані пропозиції щодо удосконалення обліково інформаційного забезпечення процесу управління розрахунками з контрагентами дозволять усунути недоліки в документальному оформленні розрахунків, забезпечать узгодження між сторонами, первинними та зведеними документами та налагодять систематизацію наведеної в них інформації. Одночасно робиться висновок, що при наявності достатньої кількості якісної облікової інформації дотримується виконання договірних зобов’язань суб’єктами господарювання, підвищується відповідальність за дотримання платіжної дисципліни, прискорюється оборотність обігових коштів. RU: В статье с научной точки зрения рассматривается одна из ключевых проблем экономической безопасности предприятия в процессе хозяйственной деятельности, учета обязательств, анализа и отчетности, с точки зрения влияния рисков на систему организации и ведения учета текущей задолженности по расчетам с контрагентами. На основании детального научного анализа учета и отчетности расчетов с поставщиками и подрядчиками, и собственных исследований автор рассматривает учетно-информационное обеспечение процесса управления расчетами с контрагентами. Предоставлены научно обоснованные предложения по совершенствованию учетно-информационного обеспечения процесса управления расчетами с контрагентами, которые позволят устранить недостатки в документальном оформлении расчетов, обеспечат согласования между сторонами, первичными и сводными документами и наладят систематизацию приведенной в них информации. Одновременно делается вывод, что при наличии достаточного количества качественной учетной информации четко выполняются договорные обязательства субъектами хозяйствования, повышается ответственность за соблюдение платежной дисциплины, ускоряется оборачиваемость оборотных средств. EN: The article from the scientific point of view is considered one of the key problems of financial security of enterprise in the process of economic activities, accounting of commitments, analysis and reporting, from the point of view of the impact of risks on the organization and accounting of your outstanding payments to contractors. Based on a detailed scientific analysis of accounting for payments to suppliers and contractors and his own research, the author examines the formation and role of accounting information in modern conditions, including external and internal financial reporting, accounting and information support of the process of managing payments to contractors. This scientifically based proposals and recommendations on designated issues, in particular concerning the rational use of document management for accounts payable and the use of aprogram. This proposal will strengthen the information security of the enterprises will improve the accounting work of the enterprise relative to expediting the processing and movement of documents to accounts payable. On the basis of these studies, with the aim of reducing the amount payable, the Statute granted which has expired, it is proposed to use an analytical document - "the Sheet control accounts payable with counterparties". For effective operational information for management and control of financial-settlement operations, the terms and conditions of repayment of debt, and simplifying the verification of information on the objects of delivery, the proposed disaggregation of the information by applying analytical sub-accounts to the account 63 "Settlements with suppliers and contractors": "Liabilities to domestic suppliers whose payment deadline has not yet come" and "Obligations whose statute of limitations has expired”. To enhance the informativeness of reporting and quality assessment of future economic relations, this work suggests that the overdue accounts payable reflect the way of detail in the article "Current payables for goods, works, services" in form № 1 "Balance sheet (statement of financial state)" by adding additional articles, "including the limitation period of which has expired".
Accounting and information support of settlement management with contractors
Keywords: облік; розрахунки; контрагенти; інформаційне забезпечення; учет; расчеты; контрагенты; информационное обеспечение; accounting; calculations; contractors; information support